Clinical researchSmall dense LDL cholesterol and apolipoproteins C-II and C-III in non-diabetic obese subjects with metabolic syndrome - Filippatos, Theodosios D.; Tsimihodimos, Vasilis; Kostapanos, Michalis; Kostara, Christina; Bairaktari, Eleni T.; Kiortsis, Dimitrios N.; Tselepis, Alexandros D.; Elisaf, Moses S. (Archives of Medical Science, 2008)
Introduction: Apolipoprotein (apo) C-II is considered as an important activator of lipoprotein lipase (LPL) and is required for efficient lipolysis of triglyceride (TG)-rich lipoproteins. In contrast, excess apo C-II inhibits LPL-mediated hydrolysis of TGs. Apo C-III is an inhibitor of LPL activity. These effects may influence the plasma levels of atherogenic small dense low-density lipoprotein cholesterol (sdLDL-C), since TG concentrations are markers of this subfraction. Material and methods: We examined the possible influence of apo C-II and C-III plasma levels on sdLDL-C concentration in obese patients with metabolic syndrome (MetS). Plasma apo C-II and C-III were determined by an immunoturbidimetric assay. Obese subjects (n=73) with MetS but without any clinically evident cardiovascular disease were enrolled. Results: TG, apo C-II and C-III plasma levels progressively increased when study participants were divided according to sdLDL-C tertiles (P<0.001 for all 3 trends). The apo C-III/C-II ratio was relatively constant (i.e. »2.5) for all tertiles of sdLDL-C. Stepwise multiple linear regression analyses showed that apo C-III levels independently correlated with TG levels, while TG and apo B levels were independently associated with sdLDL-C concentrations. Apo C-II and C-III significantly correlated with sdLDL-C in univariate analysis, but not in multivariate analysis. Conclusions: Apo C-II and C-III levels are not independent predictors of sdLDL-C levels in obese subjects with MetS.